Optimal combination of treatment modality to increase survival in patients with anaplastic thyroid carcinoma: A STROBE compliant retrospective study. Issue 25 (June 2018) - Lee, Joon-Hyop; Ahn, Hee Kyung; Seok, Jae Yeon; Lee, Kyu-Chan; Chun, Yong Soon; Chung, Yoo Seung; Lee, Young Don
Abstract : Abstract: There is little consensus on the optimal treatment approach for newly diagnosed patients. The present study aims to provide additional evidence by evaluating a series of patients diagnosed with anaplastic thyroid carcinoma (ATC) and analyzing factors related to increased survival. This was a retrospective cohort report structured according to the Strengthening the Reporting of Observational studies in Epidemiology (STROBE) guideline. Demographics, chief complaint, history of prior thyroid cancer, stage at presentation, management modalities (surgery, chemotherapy, radiotherapy, or observation), completeness or resection, and survival period since initial diagnosis were reviewed for patients with documentation of histologic ATC diagnosis between 2003 and 2016. The median survival period for 34 patients (11 males, 23 females) was 93.5 days. Patients aged 70 or younger (111 days) tended to survive longer than those older 70 (88 days) ( P  = .081). Observation, surgery only, radiotherapy only, and chemo-radiotherapy after surgery group showed median survival of 88 days, 49 days (range 14–528), 61.5 days, and 225 days, respectively. There was also no significant difference in survival between the 10 (29.4%) stage IVb (225 days) and 23 (67.7%) IVc (88 days) patients ( P  = .242). The median survival of the R1 resection group was 514 days while that of the R2 group was 102 days ( P  = .338). There were no significant difference between patients with the de novo ATC (112 days) and patients with papillary thyroid carcinoma origin ATC (99 days) ( P  = .297). Results from our series of 34 patients with ATC show that more intense combination of surgery and chemo-radiotherapy tends to secure a longer survival period. Therefore we recommend a multi-modality approach after a comprehensive consultation with the patient.